Npure Hair Oil :"Pemanfaatan Virgin Coconut Oil (Vco) Menjadi Minyak Rambut Untuk Meningkatkan Pendapatan” - Ika Wisudawaty; Pahrul Pahrul; Sumiati Tahir; Nur halim; Mahmuddin Mahmuddin (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
The creative industry in Indonesia has experienced rapid growth in recent years, leading to increased business competition and encouraging innovation in product marketing. This trend has driven many entrepreneurs to develop products that are not only appealing but also offer added value. One such innovation in the beauty sector is the development of hair oil made from Virgin Coconut Oil (VCO). This product utilizes VCO, which is rich in vitamin E, lauric acid, and antioxidants, all known for their benefits in nourishing hair and maintaining scalp health. The natural composition of VCO makes it a safe choice for individuals who wish to avoid harmful chemicals commonly found in hair care products. What makes this business unique is its formulation that combines VCO with almond oil. Although VCO is widely used in various beauty products, hair oil that blends it with almond oil remains rare in the market. Almond oil, which is also rich in vitamin E and essential fatty acids, helps moisturize the hair, reduce hair loss, and strengthen the hair roots. This combination is expected to provide maximum benefits for hair care. The method used in this study involved a product trial with several participants in the city of Makassar. The trial lasted for one week, aiming to evaluate the product’s effectiveness in delivering the intended benefits. The results of the study indicate that an optimal formulation was successfully developed, resulting in a high-quality hair oil with maximum benefits. Additionally, this product holds potential to increase community income by utilizing the abundant coconut resources, thereby adding value to the local economy